EATING HABITS OF OVERWEIGHT CHILDREN AT SEKOLAH DASAR BUDYA WACANA, YOGYAKARTA - Raymond Dwi Prasetya; Yoseph Leonardo Samodra; Istianto Kuntjoro (Faculty of Medicine Universitas Kristen Duta Wacana, 2020)
Background: Childhood obesity is related to chronic diseases in the future, which could be prevented through changes in eating habit. Strategy in eating behaviour needs an in-depth understanding on contributing factors to unhealthy eating habits in school-age children. Meanwhile, evidence on those factors, especially related increased calorie intake, is still scarce in Indonesia. Objective: This study is aimed to explore the eating habit of primary school students with obesity in a private school in Yogyakarta. Method: A qualitative interview involving parents of obese children was performed at Sekolah Dasar Budya Wacana in January 2020. The transcripts were analysed using a thematic approach to acquire major themes related to the cause of unhealthy eating habits. Results: From 11 parents, there are two major themes developed, which are unhealthy eating habits and parental influences. There are two unhealthy eating habits discovered in this study, which are irregular mealtime and unhealthy food choices. Parental influence which commonly found in children with obesity is permissive parenting style. Conclusion: This study found similar result with previous studies on unhealthy food choices. However, irregular mealtime in this study is not consistent with other literatures which shows a lack of association with childhood obesity, hence need further research to explore the relationship. Permissive parenting style, which commonly found in younger population also play an important role in children unhealthy food choice. This study revealed that health behaviour change strategy in obese children should consider focussing on healthy food preferences with support from parents and family.